Whether Forward Exchange Rate is an Unbiased Predictor for Future Spot Rate: an Empirical Study for testing SEH - Shuailin, Wu (2010)
Abstract This dissertation aims to investigate the relationship with forward exchange rate and future spot exchange rate by six bilateral exchange rates from ERM crisis happened (1992) to the end of credit crisis (2009). The empirical test in this paper based on Fama’s equation with unit root test (Augmented Dickey-Fuller test) and cointegration test (Johansen Cointegration test) which are ignored in earlier study.